Dried fish packed in plastic bags or pouches - Mumbai Archive Project Team (Jio Institute, 2024)
Dried fish may be packaged in plastic bags or pouches with airtight seals to protect them from moisture and contaminants. Processed fish products are sold to wholesalers or exported to other regions.